2020
DOI: 10.3389/fped.2020.00286
|View full text |Cite
|
Sign up to set email alerts
|

Elective Cesarean Section on Term Pregnancies Has a High Risk for Neonatal Respiratory Morbidity in Developed Countries: A Systematic Review and Meta-Analysis

Abstract: Background: Cesarean section (CS) is one of the most recurrently carried out surgical procedures in modern obstetrics. Worldwide, about 18.5 million CSs are conducted annually. Of this, 21-33% are performed in middle-and high-income countries. The effectiveness of the CS in preventing maternal and prenatal mortality and morbidity is medically justifiable. However, cesarean delivery without demanding obstetrical indications, by mere maternal request, may expose the child to several risks over benefits. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
2
18
0
6
Order By: Relevance
“…This study also showed that early‐term birth was associated with an increased risk of respiratory distress among neonates delivered via cesarean delivery at term with no indications for early delivery. This result is consistent with previous studies that showed the effects of early‐term birth on neonatal respiratory morbidity 34 , 35 and highlights the significance of the increasing frequency of early‐term births on neonatal health.…”
Section: Commentsupporting
confidence: 93%
“…This study also showed that early‐term birth was associated with an increased risk of respiratory distress among neonates delivered via cesarean delivery at term with no indications for early delivery. This result is consistent with previous studies that showed the effects of early‐term birth on neonatal respiratory morbidity 34 , 35 and highlights the significance of the increasing frequency of early‐term births on neonatal health.…”
Section: Commentsupporting
confidence: 93%
“…For example, the incidence of postoperative ileus after cesarean section lies around the 12%. 23 In addition, there is a higher risk of postpartum sepsis, especially in an emergency cesarean section, and women who deliver by cesarean section are more likely to be admitted to the ICU. 23,24 Subsequent cesarean section carry even higher risks.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…However, the risk of bleeding in a planned cesarean section is lower in comparison to a planned vaginal birth (respectively 1.1% and 6.0%). 23 Apart from adverse effects on the mother, a cesarean section can have disadvantages for the child as well.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Recent systemic review and meta-analysis have concluded that newborn delivered by ECS is at a higher risk of developing respiratory complications in comparison to normal vaginal delivery (NVD). 1 Changes taking place in NVD contributing towards smooth neonatal respiratory transition include upsurge of catecholamine, corticosteroid release, mechanical chest compression by the birth canal and expression of sodium channel on foetal lung epithelium. 2,3 In ECS, lack of this catecholamine upsurge contributes to surfactant deficiency, making the neonatal transition more complex leading to increased incidence of NRM.…”
Section: Introductionmentioning
confidence: 99%